A successful treatment of a lobar atelectasis in a patient with cystic fibrosis. Issue 11 (6th September 2022) - Daccò, Valeria; Sciarrabba, Calogero Sathya; Corti, Fabiola; Rosazza, Chiara; Malfitano, Anna; Borzani, Irene; Colombo, Carla
Abstract: Lobar atelectasis may be a complication of pulmonary exacerbations in cystic fibrosis (CF). There are no established guidelines on the management of this condition in patients with CF. Therapeutic bronchoscopy with recombinant human deoxyribonuclease (rhDNase) instillation has been described to be successful in patients not responding to conservative measures. We describe a case of a young man with CF, with previously mild impaired lung function, presenting with cough, desaturation, and worsening dyspnea, persisting for over 6 weeks, despite conservative therapy. Thoracic imaging showed right lower lobe atelectasis, which was successfully treated with bronchoscopy and instillation of rhDNase. Long‐term resolution of the atelectasis was confirmed with chest magnetic resonance imaging follow‐up.